Paleogeography And Sedimentation Dynamics Of Ujoh Bilang-Batubelah Limestone Member, Upstream Mahakam River, Ujoh Bilang Area, East Kalimantan Province - Indra Novian; Herning Dyah Kusuma Wijayanti (Geological Engineering Department Universitas Gadjah Mada, 2015)
-